Comparative antagonistic potential of some biocontrol agents against sheath blight of rice - and A.P. SINHA, ASHRAF All KHAN (Indian Phytopathology, 2005)
The present investigation was undertaken to evaluate biocontrol potential of isolates of Trichoderma spp. and some commercial formulations of biocontrol agents against Rhizoctonia solani causing sheath blight of rice. Maximum reduction in disease severity (70.57%) and incidence (38.25%) were observed with foliar sprays of Contaf. Among bioagents, foliar sprays with T.harzianum (a rice leaf isolate) was found most effective in reducing sheath blight (44.35-52.37%) and increasing grain yield (20.25-23.13%) and 1000 grain weight (6.36.7.35%). T.virens (rice rhizosphere isolate) was found next in order of. effectivity against the disease showing 38.27-43.03 and 11.70-21.69% reduction in disease severity and incidence, respectively. Reduction in sheath blight severity with Sanjeevni and Pant Bioagent 3 were not significant by difference in their efficacy.